Bioassay guided isolation of antioxidative compounds from two rutaceous species Melicope glabra (Blume) T.G. Hartley and Micromelum minutum (G. Forst) Wight and Arn - Kassim, Nur Kartinee (2013)
Research on the application, characteristics and sources of natural antioxidants especially phenolic had received great interest as synthetic antioxidants were reported to give adverse health effects. Melicope glabra (Blume) T.G.Hartley and Micromelum minutum (G. Forst.) Wight and Arn. (Rutaceae) are edible plants of the Rutaceae family. Both plants are traditionally used in the treatment of various diseases and known to contain a number of rutaceous compounds such as coumarins, lignans and alkaloid. To date, the reports on the bioactive compounds responsible for their medicinal properties are very limited. Thus, the search to identify bioactive compounds particurlarly as antioxidant agent from these unexplored plants are really significant. A bioassayguided isolation technique by 1, 1-diphenyl-2-dipicrylhydrazyl (DPPH) radical was used to locate and identify the presence of antioxidant components in various extracts of these plants. The three extracts (hexane, ethyl acetate and methanol) of M. glabra were screened for antioxidant properties by four different assays; DPPH free radical scavenging, oxidation of β-carotene and linoleic acid, oxygen radical antioxidant capacity (ORAC) and total phenolic content (TPC). The results showed that the ethyl acetate and methanol extracts possessed very good antioxidant potential and were selected for activity-guided fractionation. The DPPH IC50 values obtained for ethyl acetate and methanol extracts were 24.81 and 13.01μg/mL with the antioxidant activity of 99.5 and 93.0% on the β-carotene bleaching assay as compared to α-tocopherol (100%). They also gave high ORAC values (1521 and 2182 μmol TE/g) for the former and latter, respectively. The column chromatograhic separation on active extracts gave five active fractions namely ME 21, ME 24, ME 31, MM 13 and MM 16 with the DPPH IC50 values of 17.22, 58.98, 30.21, 17.72 and 49.13 μg/mL respectively. The methanolic extract of M. minutum also exhibited good antioxidant activities against radical scavenging, β-carotene bleaching and ORAC assays by exhibiting values of 54.3 μg/mL, 55.19% and 5123 μmol TE/g respectively. The M. minutum fraction gave the DPPH IC50 of 168.9 μg/ml and ORAC value of 5.75%. Phytochemical investigation on Melicope glabra active fractions led to the isolation of ten compounds including one lignan sesamin (36), a number of coumarin derivatives (umbelliferone (37), scopoletin (40), a new pyranocoumarin, glabranin (41), scoporone (42), 6,7,8-trimethoxycoumarin (43) and marmesin (44)) together with two new glycosides (3-β-D-galactopyranosyl)-O-(2-hydroxy-4-methylenedioxy) cinammate (38) and 22-hydroxyfurost-5-ene-(6→O)-α-methylalanyl-3-O-β- glucopyranoside (39)). Meanwhile, phytochemical study on M.minutum methanol bark extract succesfully yielded one lignan sesamin (45) which was previously isolated from the earlier plant,two new coumarins (hydramicromelinin (46) and micromelinin (47)) along with three glycosides (marmesin glycoside (48), maltose (49) and sucrose (50)). Five of the compounds were identified as new since there has been no previous reports on these compounds. The structure elucidation of the isolates were characterized by different spectroscopic techniques such as UV (ultraviolet), IR (infrared), MS (mass spectra), NMR (nuclear magnetic resonance) and comparison with published data. The isolated compounds, sesamin (36), umbelliferone (37), scopoletin (40),glabranin (41), 3-(β-D-galactopyranosyl)-O-(2-hydroxy-4-methylenedioxy) cinammate (38) and 22-hydroxyfurost-5-ene-(6→O)-α-methylalanyl-3-O-β-glucopyranoside (39) displayed DPPH IC50 values of 2508.63, 810.02, 413.19, 240.20, 323.78 and 124.13 μg/mL respectively. In the assesment of antioxidant activities by β-carotene bleaching assay on the isolated compounds,sesamin (36) displayed the most potent antioxidant with the antioxidant activity of 95.9%. The antioxidant activity observed for other compounds (glabranin (41), umbelliferone (37) and scopoletin (40)) were 74.9, -44.0 and -54.2 % respectively. Umbelliferone (37) and scopoletin (40) showed slightly prooxidant activities. Two isolated compounds from M.minutum namely hydramicromelinin (46) and marmesin glycoside (48) were also exhibited prooxidant behavior with the antioxidant activity of -116.35 and -34.18%, respectively. The measurement of scavenging activity by ORAC method revealed umbelliferone (37) as highly potential antioxidant agent with the ORAC value 24,965 μmol TE/g compared to ascorbic acid (5785 μmol TE/g ). Hydramicromelinin (46) also showed strong antioxidant activity with the ORAC value of 5539 μmol TE/g. The ORAC values recorded for other compounds; glabranin (41), scopoletin (40),sesamin (36) and marmesin glycoside (48) were 2883, 2007, 2319 and 4031μmol TE/g respectively.